Faktor Penentu Financial Distress pada Perusahaan Sektor Pertanian yang Terdaftar di BEI Periode 2015-2019 - Nurul Noviyani; Eka Yulianti (Studi Ilmu Manajemen dan Organisasi, 2022)
Purpose: The motive of this studiesto determine impact of ROA, CR, DER on financial distress the use of Altman Z-score approach. Research Methodology: This studies is a quantitative research using panel data dimensions, descriptive and associative data analysis, non probability sampling and purposive sampling techniques, as well as using the random effects model analysis method on Eview10. Result: The effects of this study suggest ROA has positive effect on the Z-Score, CR has positive effect on the Z-Score and DER has negative effect on the Z-Score, simultaneously ROA,CR,DER afffect financial distress. Limitations: The limitations in this study are best performed within the argicultural area listed on Indonesia Stock Exchange for the 2015-2019 period in line with the researcher’s criteria by the use of  ROA,CR,DER variabels in predicting the potential for financial distress and using Altman Z-score technique which has the opposite interpretation. Contribution: Research contribution to provide information for argicultural sector companies to improve performance so as to avoid potential financial distress, be considered for investor earlier than making an investment so the get income, and as facts for in addition research.